Evaluación de enraizantes y fertilizantes foliares en el cultivo de coliflor (Brassica oleracea var. Botrytis L.) en la parroquia Santa Martha de Cuba, provincia del Carchi - Cuaspud Velasco, Silvia Eugenia (2018)
VII. SUMMARY The present investigation was carried out in the parish of Santa Martha de Cuba, Canton Tulcán, Province of Carchi, latitude north 00 ° 40'00 "and longitude west 77045'00" and altitude 2895 masl. The genetic material evaluated was the Snowball variety, the factors studied were three doses of rooting and three doses of fertilizer (low, medium and high). The objective was: determine the effect of the application of rooting and foliar fertilizers on the production of the cauliflower crop (Brassica oleracea var. Botrytis). The theoretical methods were used: Inductive-deductive, synthesis analysis and the empirical so-called experimental The activities carried out in the field were: soil analysis, soil preparation, delimitation of plots, transplant, plant selection, weed control, hilling, application of rooting and foliar fertilization and harvesting, the evaluated data, percentage of predation, height of the plant, plant and pellet diameter, yield and treatments were analyzed economically. It was obtained that high dose of root Nutriliq (7 cc / liter of water) presented significant averages in the evaluations of: height of plant, diameter of plant, diameter of pella and yield / plant and yield / ha. In the doses of foliar fertilizer (Fetrilon C) the average dose (1.5 g / liter of water) reported higher plant height, plant diameter, pellet diameter and yield, acting as a nutrient and corrector of deficiencies due to its wide variety of microelements, the dose to correct deficiencies is low. In the economic analysis, the T8 treatment was registered (high Rooting dose + mean Fertilizer dose), with the highest economic benefit of $ 22,413.13 USD per hectare.